2020
DOI: 10.1016/j.neuropharm.2020.108151
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional pharmacological perturbations of the noradrenergic system differentially affect tactile detection

Abstract: The brain neuromodulatory systems heavily influence behavioral and cognitive processes.Previous work has shown that norepinephrine (NE), a classic neuromodulator mainly derived from the locus coeruleus (LC), enhances neuronal responses to sensory stimuli. However, the role of the LC-NE system in modulating perceptual task performance is not well understood. In addition, systemic perturbation of NE signaling has often been proposed to specifically target the LC in functional studies, yet the assumption that loc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 94 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…Recent optogenetic and pharmacological work has shown that activating the LC–NE system enhances detection/discrimination sensitivity ( Gelbard-Sagiv et al, 2018 ; Rodenkirch et al, 2019 ; McBurney-Lin et al, 2020 ). Thus, LC–NE acting on early sensory areas (i.e., primary sensory thalamus, primary sensory cortex) likely affects perceptual decision making ( McBurney-Lin et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent optogenetic and pharmacological work has shown that activating the LC–NE system enhances detection/discrimination sensitivity ( Gelbard-Sagiv et al, 2018 ; Rodenkirch et al, 2019 ; McBurney-Lin et al, 2020 ). Thus, LC–NE acting on early sensory areas (i.e., primary sensory thalamus, primary sensory cortex) likely affects perceptual decision making ( McBurney-Lin et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since we observed that LC-NE activity diverged in response to reward or error and that the magnitude of this difference correlated with learning, we next wanted to examine how manipulating the activity of these neurons altered reversal behavior in the maze task. Pharmacological agents selective for alpha-2 (α2) adrenergic receptors were directly infused into the LC on reversal sessions to transiently silence (clonidine, α2-agonist) or enhance (idazoxan, α2-antagonist) LC activity through an autoreceptor-dependent mechanism (Figure 2A, B) 40,41 . Mice were assigned to one of three treatment groups: clonidine, idazoxan, or control (saline) and received a cannula infusion, according to their group, on each reversal day (R1-R4) before the maze task (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…On days of infusion (Fig. 2B), 600 nl of 0.9% sodium chloride (Hospira, St. Jude Pharmacy), α2-antagonist idazoxan hydrochloride (5 mg/ml, adapted from 68 , Sigma, I6138), or α2-agonist clonidine hydrochloride (5 mM, adapted from 40 , Sigma, C7897) were infused bilaterally (200 nl/min, 2 min wait) using a dual-syringe (5 μl, Hamilton, 87931) microinjection pump (KD Scientific, 14-831-211) and plastic tubing (P1 Technologies, 8F023X041P01) immediately before the maze task. Testing prior to experiments determined drug dosages that did not cause gross impairments in behavior.…”
Section: Methodsmentioning
confidence: 99%
“…To suppress LC function, we used two manipulations with different modes of action: local, stereotaxic-guided LC infusion of clonidine and systemic injection of the LC norepinephrine-depleting toxin DSP4 ( N -(2-chloroethyl)- N -ethyl-2-bromobenzylamine hydrochloride). The rationale for this was based on previous publications showing that clonidine suppresses LC noradrenergic neurons by activating the inhibitory α2-adrenoceptor 34 37 , while DSP4 treatment selectively degrades the LC noradrenergic function to 10–30% of its normal value 38 . In the clonidine experiments (Extended Data Fig.…”
Section: Methodsmentioning
confidence: 99%